Barley SIX-ROWED SPIKE3 encodes a putative Jumonji C-type H3K9me2/me3 demethylase that represses lateral spikelet fertility - Hazel Bull (Nature Portfolio, 2017)
The VRS genes of barley control the fertility of the lateral spikelets on the barley inflorescence. Here, Bull et al. show that VRS3 encodes a putative Jumonji C-type histone demethylase that regulates expression of other VRS genes, and genes involved in stress, hormone and sugar metabolism.